Ultrasound-Responsive Materials for Drug/Gene Delivery - Cai, Xiaowen; Jiang, Yuan; Lin, Mei; Zhang, Jiyong; Guo, Huanhuan; Yang, Fanwen; Leung, Wingnang; Xu, Chuanshan (Frontiers in Pharmacology, 2020)
Ultrasound is one of the most commonly used methods in the diagnosis and therapy of diseases due to its safety, deep penetration into tissue, and non-invasive nature. In the drug/gene delivery systems, ultrasound shows many advantages in terms of site-specific delivery and spatial release control of drugs/genes and attracts increasing attention. Microbubbles are the most well-known ultrasound-responsive delivery materials. Recently, nanobubbles, droplets, micelles, and nanoliposomes have been developed as novel carriers in this field. Herein, we review advances of novel ultrasound-responsive materials (nanobubbles, droplets, micelles and nanoliposomes) and discuss the challenges of ultrasound-responsive materials in delivery systems to boost the development of ultrasound-responsive materials as delivery carriers.